Pengaruh Pendekatan Realistic Mathematics Education Berbantuan Cabri 3D untuk Meningkatkan Kemampuan Spasial Siswa SMP Negeri 10 Medan - Irene Yoseva Sinaga; Fevi Rahmawati Suwanto (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Students' low spatial abilities result in difficulties in understanding geometric concepts, especially in visualizing and analyzing spatial figures and the relationships between objects. As a result, students' abilities in solving mathematical problems related to space are less than optimal. This study aims to analyze the effect of the Realistic Mathematics Education (RME) approach assisted by Cabri 3D on students' spatial abilities. This study was conducted at SMP Negeri 10 Medan. The population in this study were all 12 ninth-grade students of SMP Negeri 10 Medan. The sample in this study was class IX-G as the experimental class and IX-F as the control class. This study used an quasi experimental method with a pretest-posttest control group design. The research instrument was a spatial ability test before and after treatment. Data analysis used an independent sample t-test. The results of the analysis showed that the average spatial ability of students in the experimental class was higher than the control class with a value of 82.9688 > 76.0156 and sig. = 0.001 < 0.05. These findings indicate that the Cabri 3D-assisted RME approach significantly improves students' spatial abilities in geometry.